Effects of internalized stigma on symptoms and quality of life in schizophrenic patients; mediated by dysfunctional attitude - Shaheen, Sajida; Amin, Rizwana (International Journal of Health, 2016)
The objective of this study was to determine the effects of internalized stigma on symptoms, quality of life of schizophrenic patients; mediated by dysfunctional attitude. A descriptive correlational research design was used to investigate the relationship between symptoms, quality of life and dysfunctional attitude in schizophrenic patients. Linear regression was used to investigate the mediational effects of dysfunctional attitude. Purposive sampling technique was used for the selection of the participants. The study was conducted on diagnosed schizophrenic patients from psychiatry ward of Nishtar Hospital Multan, Fountain House Rehabilitation Centre Lahore and Punjab Institute of Mental Health Rehabilitation Centre Lahore. The sample of the study was 50 registered patients of schizophrenia. Calculated sample size was 50 schizophrenic patients among them 34 were Males and 16 were Females. Internalized Stigma of Mental Illness Scale was used to see the effects of stigma on schizophrenic patients (ISMI, Ritsher, 2003), along with Positive and Negative Syndrome Scale was used to evaluate the positive and negative symptoms in schizophrenic patients (Kay, et al., 1987), World Health Organization Quality of life BREF Scale (WHOQOL-BREF, 2003) was used to assess the quality of life of schizophrenic patients, along with another scale of Dysfunctional Attitude Scale (DAS, Weissman, 1978) was also used to assess the cognitive functioning of the schizophrenic patients. Studies showed that internalized stigma had significant positive correlation with dysfunctional attitude and negative significant correlation with symptoms and quality of life of schizophrenic patients. Internalized stigma had strong significant effects on the symptoms, quality of life and dysfunctional attitude. Studies also showed that people with mental illness has to face negative stereotype, rejection and finally alienation from society because of stigma which is a big hurdle in their process of recovery and treatment.Â